Navigating through apertures: perceptual judgements and actions of children with Developmental Coordination Disorder. Issue 6 (16th October 2016) - Wilmut, Kate; Du, Wenchong; Barnett, Anna L.
Abstract: Passing through a narrow gap/aperture involves a perceptual judgement regarding the size of the gap and an action to pass through. Children with DCD are known to have difficulties with perceptual judgements in near space but whether this extends to far space is unknown. Furthermore, in a recent study it was found that adults with DCD do not scale movements when walking through an aperture in the same way as their peers. The current study, therefore, considered perceptual judgements and motor behaviour of children with DCD while looking at or walking through apertures. Twenty‐nine children with DCD and 29 typically developing (TD) children took part. In Experiment 1, participants completed a perceptual task, where they made passability judgements. Children with DCD showed a significantly smaller critical ratio (aperture size at which a participant first rotates the shoulders to pass through) compared to their TD peers. In Experiment 2, participants completed an action task where they walked through the same apertures. Children with DCD showed a significantly larger critical ratio than TD peers when body size alone was accounted for. Taken together these results suggest that perception within a static context is different from that within a dynamic context for children with DCD. However, despite this difference we have demonstrated a clear relationship between perception and action in children with DCD. A video abstract of this article can be viewed at:https://youtu.be/SABXFrAJtF8 Abstract : Children with and without DCD (aged 7‐17years) completed perceptual passability judgements regarding passage through an aperture and also their passage through the same apertures was measured. The critical ratio in the perceptual task was smaller in the children with DCD compared to the TD group while in the action task the critical ratio was larger in the children with DCD compared to the TD group. Our results demonstrate that perception within a static context is different from behaviour in an action context. Despite this difference we found clear evidence for a relationship between perception and action in children with DCD.